Bezpečnost vybraného výrobního uzlu automatizované linky pro výrobu automobilových karosérií - Plachý, Štěpán (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2021)
Tato diplomová práce se zabývá bezpečností vybraného výrobního uzlu automatizované linky pro výrobu automobilových karosérií. V první části práce je řešena rešerše relevantních směrnic Evropského parlamentu a Rady. Následuje systémový rozbor řešené problematiky a popis zařízení. V další části práce je provedena analýza harmonizovaných norem v oblasti bezpečnosti výrobní linky. Dále je provedena identifikace nebezpečí, odhad a posouzení rizik. V poslední části práce jsou vytvořeny variantní návrhy zabezpečení pracoviště, technicko-ekonomické posouzení variant a výpočty pro výslednou variantu pracoviště.

This master’s thesis deals with the safety of a selected production node of an automated body production line. The first part is focused on a recherche of relevant directives by the Council and the European parliament. Follows a systems analysis of a solving issue and description of the production line. In the next part of the thesis, there is an accomplished analysis of harmonized standards in the safety of the production line. Furthermore, there is made hazard identification, risk estimation and risk assessment. The last part of the thesis is focused on a variants creation of safety of a workplace, technical-economic consideration of variants and computations for a final variant of the workplace.
Safety of a selected production node of an automated body production line
Keywords: Automatizovaná linka; svařování karoserie automobilu; harmonizované normy; analýza rizik; bezpečnost výrobního uzlu.; Automated production line; car body welding; harmonized standards; risk analysis; safety of a production node.